Structural Characterization of Nanocrystalline Sb-Doped SnO2 Xerogels by Multiedge X-ray Absorption Spectroscopy - Geraldo, V. [UNESP]; Briois, V.; Scalvi, Luis Vicente de Andrade [UNESP]; Santilli, C. V. [UNESP] (Amer Chemical Soc, 2010)
Multiedge XAS data are presented for Sb-doped SnO2 xerogels dried at 200 degrees C and fired at 550 degrees C, aiming to determine the location of antimony doping in the host matrix and then to understand the role that the intentional impurity plays in the structure and properties of the tin oxide based materials. Xerogel processing at 200 degrees C leads to the original trivalent antimony, used for the xerogel preparation to the Sb-v oxidation state, mainly for low doping levels ([Sb] <= 4 atom %). As the doping level increases, a significant amount of antimony remains in the trivalent oxidation state. Upon firing at 550 degrees C, the antimony is present mainly as Sb-v, independent of the doping level. The analysis of EXAFS data recorded at the Sn and Sb K edges leads to the conclusion that doping with Sb for a level of less than 4 atom % favors crystallite growth, concomitant with a strong dominance of the Sb-v oxidation state. Besides, the pentavalent antimony is located at internal sites of the SnO2 nanocrystallites. The EXAFS spectra of the higher ([Sb] > 4 atom %) doped samples can always be fitted by a linear combination of the spectra corresponding to the Sbv site in solid solution and the spectra corresponding to the sample where Sb-III is chemically grafted at the surface of the SnO2 crystallite. This Sb-III segregation also agrees with the low electrical conductivity reported for sol-gel deposited films, because it generates a barrier at the grain boundary, inducing a very high electron scattering and, thus, a low electron mobility.